2020
DOI: 10.1007/s41748-020-00179-1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Daily Weather on the Temporal Pattern of COVID-19 Outbreak in India

Abstract: The COVID-19 pandemic has spread obstreperously in India. The increase in daily confirmed cases accelerated significantly from ~ 5 additional new cases (ANC)/day during early March up to ~ 249 ANC/day during early June. An abrupt change in this temporal pattern was noticed during mid-April, from which can be inferred a much reduced impact of the nationwide lockdown in India. Daily maximum (TMax), minimum (TMin), mean (TMean) and dew point temperature (TDew), wind speed (WS), relative humidity, and diurnal rang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 65 publications
(64 reference statements)
1
41
0
Order By: Relevance
“…Researchers have done a lot of studies to determine which factors affect to transmission of COVID-19 by evaluating these data together with various parameters. The weather variables are good indicators to forecast COVID-19 cases in following days (Gupta et al 2020a , b ; Li et al 2020a , b ; Rohrer et al 2020 ; Wu et al 2020 ). Table 1 shows the results of existing literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have done a lot of studies to determine which factors affect to transmission of COVID-19 by evaluating these data together with various parameters. The weather variables are good indicators to forecast COVID-19 cases in following days (Gupta et al 2020a , b ; Li et al 2020a , b ; Rohrer et al 2020 ; Wu et al 2020 ). Table 1 shows the results of existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Iqbal et al ( 2020 ), Liu et al ( 2020 ), Ma et al ( 2020 ), Shi et al ( 2020 ) have studied these variables for China which is the first centre of the pandemic. Bashir et al ( 2020 ), Gupta et al ( 2020a , b ), Runkle et al ( 2020 ) have focused on US and they have employed similar variables.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, after the onset of the new pandemic, a number of studies have been carried out to investigate the possible effect of weather on the spread of COVID-19. Some of these studies have focused on specific regions and countries, such as 122 cities in China [10], Wuhan, China [11], Mainland China [12], Jakarta, Indonesia [13], India [14,15], Iran [16], Brazil [17], Europe and United States [18], and Russia [19], while others have examined the effect of weather conditions on the pandemic at a global scale . Smit et al [42], who presented a comprehensive critical review of the relevant literature published in the first half of 2020, concluded that it is important for studies to include the effects of socio-economic factors and non-pharmaceutical interventions (such as government response measures) in their analysis.…”
Section: Introductionmentioning
confidence: 99%
“…https://doi.org/10.1007/s42452-020-03829-1 with a view to make it linear [101]. Usually linear and polynomial kernels are less time-consuming to perform but provide less accuracy than radial kernel [102,103].…”
Section: Model Approach For Pm Estimationmentioning
confidence: 99%